Edu Finance to Improve Financial Literacy in Rengginang MSMEs in Sumenep Regency - Syauqi, Ahmad; Mubarok, Imam Anas; Wakik, Wakik; Anshori, Syaiful (Majapahit Journal of Islamic Finance and Management, 2025)
This research aims to provide a comprehensive understanding of the basic concepts of financial management, such as transaction recording, budgeting, and cost calculations, which are expected to help MSMEs in making more appropriate business decisions. The population that is the focus of this study is all Rengginang MSMEs, totaling 42 MSMEs. The sampling technique used in this study is a saturated/census sample, the author took all respondents from the Rengginang MSME population, namely 42 respondents/MSMEs. Because it employs numerical data for descriptive statistical analysis, the research design employed in this study is quantitative. The outcomes of these computations will thereafter be contrasted with Chen and Volpe's standards for financial literacy. The study's findings indicate that financial behavior, financial awareness, and financial abilities are generally inadequate. Therefore, it is necessary to apply the Edu Finance Model for Rengginang MSMEs, which consists of Funding planning for rengginang MSMEs in Prenduan Village requires a clear written plan detailing the capital required and how the funds will be used. A profit and loss report can be prepared, providing information for rengginang MSMEs to manage their businesses. Furthermore, orderly financial record keeping will facilitate MSMEs. Feedback is needed to determine the extent to which budget allocations are in line with the plan. If not, the root cause of the discrepancy should be identified and incorporated into the next period's action plan to ensure sustainable financial management.